Enzymatic Antioxidant Defense and Polymorphic Changes in Male Infertility - Jędrzej Baszyński; Piotr Kamiński; Maria Bogdzińska; Sławomir Mroczkowski; Marek Szymański; Karolina Wasilow; Emilia Stanek; Karolina Hołderna-Bona; Sylwia Brodzka; Rafał Bilski; Halyna Tkachenko; Natalia Kurhaluk; et al. (MDPI AG, 2022)
The intensification of oxidative stress and destabilization of the antioxidative defenses of an organism is a consequence of many environmental factors. We considered aspects conditioning male reproductive potential and the functionality of enzymatic antioxidative mechanisms, i.e., superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione reductase (GR), and their correlations with Li, Be, B, Na, Mg, Al, P, K, Ca, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Se, Sr, Mo, Ag, Cd, Sn, Sb, Ba, Hg, Tl, Pb, and malondialdehyde (MDA), as well as genetic polymorphism IL-4v.C589T (rs2243250) in men with infertility (n = 76). A healthy normozoospermic control (n = 87) was also used. We assessed the impact of negative changes driven by oxidative stress on enzymatic antioxidative mechanisms as well as the role of MDA in the overall process. On this basis, we infer connections between disturbances in enzymatic antioxidative defense and reproductive potential. Based on a molecular analysis of the polymorphism of gene IL-4v.C589T (rs2243250) (chromosome 5) (PCR-RFLP), we considered the relationships among particular genotypes with the possibility of occurrence of male infertility. Concentrations of chemical elements were measured in the blood. The activity of antioxidants and MDA levels were measured in serum. In the infertile group, higher GPx activity was noted (6.56 nmoL·min−1·mL−1, control: 4.31 nmoL·min−1·mL−1; p = 0.004), while GR achieved a greater level in the control (17.74 nmoL·min−1·mL−1, infertile: 15.97 nmoL·min−1·mL−1, p = 0.043), which implies diversified efficiency of the first and second lines of defense. The polymorphism of IL-4v.C589T (rs2243250) was not directly connected with infertility because there were not any differences in the frequency of genotypes between the infertile and control group (p = 0.578). An analysis of genotypes CC and TT (polymorphism IL-4v.C589T (rs2243250)) indicated numerous correlations between antioxidants, chemical elements and MDA. Therefore, chemical economy, antioxidative defense and genetic conditions are connected and jointly shape male reproductive potential. Chemical elements influence antioxidative defense and male fertility; the most important modulators appeared to be Na, Ba, Al and B. The polymorphism of gene IL-4v.C589T (rs2243250) has a limited influence on antioxidative defense and the metabolism of chemical elements.